Overcoming Barriers To Providing Local Produce in School Lunches in Vermont - Erin Roche; Jane M. Kolodinsky (Journal of Agriculture, Food Systems, and Community Development, 2016)
Vermont is a leader in connecting its agricultural sector to its education system in order to provide schoolchildren with fresh, local produce. Adopting farm to school programs is not easier in Vermont; in fact, school administrators and food service directors cite the same barriers as can be found throughout the country. However, some communities in Vermont have worked hard to address these barriers and are succeeding in getting fresh local foods into their schools' meals. This article reviews common barriers and challenges to successful farm to school programs and describes some of the creative ways that schools in Vermont have addressed them.